STUDY OF THE ELECTROMAGNETIC IMPACT OF THE OVERHEAD TRANSMISSION LINES OF 330 KV ON ECOLOGICAL SYSTEMS - Cherkashina, Veronika; Litvinchuk, Svitlana; Lesko, Vladyslav; Kravets, Svetlana; Netrebskiy, Volodymyr; Sikorska, Olena; Mamyrbayev, Orken; Imanbek , Baglan (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
The analysis of factors and approaches to the conditioning of the electromagnetic impact of 330 kV overhead transmission lines on ecological systems has been carried out. The analysis performed enabled to reveal that the world experience, recording the introduction of the transmission lines of the carrying capacity and reduced environmental impact, including the compact and controlled self-compensating lines, is expedient to take into consideration in the process of the object design, as compared with the transmission line of the conventional construction, operated in Ukraine. The technique of electromagnetic field of the 330 kV overhead transmission lines calculation is improved for the ecological systems and to clarify the width of the sanitary protection zone. Unlike other technique, the given one takes into account the line clearance and the sag of, also this technique is universal as it enables to calculate and analyze the variation of the electromagnetic field of the overhead transmission lines of different construction not only on the line route, but also at a distance from it.